2020
DOI: 10.33087/jmas.v5i2.183
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompensasi Finansial Terhadap Kinerja Karyawan Pada PT Penggadaian (Persero) Cabang Jambi

Abstract: This research aims to find out how implementation of the financial compensation and performance job of PT Penggadaian (Persero) Branch  of Jambi. Next also to analyze implamentation and how the influence of financial compensation on performance job in PT Penggadaian (Persero) of Banch Jambi. This research uses descriptive method quantitative correlational research with the form that describes the relationship of independent variables with dependent variables. The research on the analysis tools using simple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of research conducted by (Suciaty & Rahmawati, 2014) show that financial towing premium compensation has a significant influence on the performance of ship crews. (Samudra et al, 2014) found that direct and indirect financial towing premium compensation has a positive and significant effect on the performance of the ship's crew. The results of research conducted by (Wibowo, Utomo, & Aditya, 2023) also show that financial towing premium compensation has a positive and significant effect on the performance of ship crews through job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of research conducted by (Suciaty & Rahmawati, 2014) show that financial towing premium compensation has a significant influence on the performance of ship crews. (Samudra et al, 2014) found that direct and indirect financial towing premium compensation has a positive and significant effect on the performance of the ship's crew. The results of research conducted by (Wibowo, Utomo, & Aditya, 2023) also show that financial towing premium compensation has a positive and significant effect on the performance of ship crews through job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…This is because a good career path system will trigger job satisfaction for ship crews, where job satisfaction will encourage ship crews to continue to perform well. (Samudra, Rahardjo, & Mukzam, 2014) suggest that direct and indirect financial towing premium compensation has a positive and significant effect on the performance of the ship's crew. This shows that the better the towing premium compensation system in a company, the better the performance of the company's ship crew.…”
Section: Introductionmentioning
confidence: 99%